Current trend of utilization of new generation proton pump inhibitors in gastric disorders among people in Jessore city, Bangladesh - Debendra Nath Roy, Nowrin Ferdiousi, Md.Uzzal Haque, Mosharraf Hossain, Sheikh Shahriar Rajib (Journal of Applied Pharmaceutical Science, 2016)
Proton pump inhibitors (PPIs) are the most widely prescribed class of gastrointestinal drugs as they have minimal side effects and few significant drug interactions, and are generally considered safe for long-term treatment. The proton pump inhibitors such as omeprazole, esomeprazole, pantoprazole, lansoprazole and rabeprazole have quite similar efficacy and potency. Current study was carried out at Jessore district in Bangladesh to investigate the current status of most commonly prescribed PPIs in terms of their generation, gender variation, age categorization and their preferred route of administration as well. However, esomeprazole was used by top most 70% patients, followed by 20%, 6%, 3% and 1% for omeprazole, pantoprazole, rabeprazole and dexlansoprazole respectively. 75% prescriptions were prescribed for oral route of administration. 55% male and 35% of 35-50 years aged patients are suffering from peptic ulcer diseases and uses PPIs for healing process. During proton pump inhibitor therapy, it was observed to have nausea of 30% and vomiting for 28% patients as a major side effect. This study reveals that the new generation PPIs becomes more popular for the treatment of gastric disorders among people of Jessore city, Bangladesh.
Keywords: Peptic ulcer, proton pump inhibitors, route of administration, nausea, Bangladesh.